Nanotechnology law : best practices - Brazell, Lorna (Alphen aan den Rijn, The Netherlands : Kluwer Law International, 2012)
Nanomaterials are already a commercial reality; the regulatory debate centres on the question of how to maximize the benefits they may offer while also limiting the risk from unforeseen hazards. This book clearly and comprehensively describes the range of issues relating to the legal framework and practicalities for commercial exploitation of nanotechnologies, and as such will prove of great value and importance to corporate counsel in many manufacturing sectors as well as to regulators and policy makers in environmental and trade law--Supplied by the publisher.
Includes bibliographical references (pages 257-258) and index.
Keywords: Nanostructured materials industry -- Law and legislation; Nanotechnology -- Government policy